2006
DOI: 10.1136/ard.2005.037978
|View full text |Cite
|
Sign up to set email alerts
|

Excess recurrent cardiac events in rheumatoid arthritis patients with acute coronary syndrome

Abstract: Recurrent ischaemic events and death occur more often after ACS in rheumatoid arthritis. Atypical presentation is commoner in rheumatoid arthritis. There is an urgent need to develop identification and intervention strategies for ACS specific to this high risk group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(74 citation statements)
references
References 40 publications
4
64
0
6
Order By: Relevance
“…This is evidenced by a higher incidence of congestive heart failure, coronary artery disease and myocardial infarction (frequently silent), as well as sudden cardiac death (10,16). In contrast, only one study has shown that patients with RA did not have excess mortality due to acute myocardial infarction compared with general population (17).…”
Section: Discussionmentioning
confidence: 92%
“…This is evidenced by a higher incidence of congestive heart failure, coronary artery disease and myocardial infarction (frequently silent), as well as sudden cardiac death (10,16). In contrast, only one study has shown that patients with RA did not have excess mortality due to acute myocardial infarction compared with general population (17).…”
Section: Discussionmentioning
confidence: 92%
“…1 Recent, mounting evidence, associates RA with excessive cardiovascular morbidity and mortality including acute coronary syndromes (ACS), heart failure and coronary death. 2,3 The causes for this are likely to be several and include a high prevalence of classical and non-traditional cardiovascular (CV) risk factors. [4][5][6][7] Hypertension (HT), the most important classical risk factor for ACS and stroke, 8 is particularly prevalent in RA.…”
Section: Introductionmentioning
confidence: 99%
“…Atypical presentation is commoner in rheumatoid arthritis. There is an urgent need to develop identification and intervention strategies for ACS specific to this high risk group 28 .…”
Section: Atypical Presentationmentioning
confidence: 99%